Organosilicon polymer-derived ceramic fibers: fabrication and molecular structure investigations - Ren, Zhongkan (Kansas State University, 2020)
As humans entered 21st century, the energy crisis has gained more attention and reached a critical situation that may impede the further innovation of science and technology. Along with the development of the Internet and wireless communication, electronic devices, from automated production robots down to small consumer electronics, are overtaking our lives at a rate that none of the conventional industries can compete with. This leads to the ever-growing demand for energy production, transportation, and storage. In addition to the investigations on clean or renewable energy sources, more researches are promoting the efficiency of generating or utilizing the already existed forms of energy. Aerospace related development and applications consume a significant amount of resources. As a critical unit of aerospace application, turbine engines may be effectively advance by the reliable high-temperature components in not only the performance but the efficiency. Fiber-reinforced ceramic matrix composites (FRCMCs) are proposed as the next-gen material of turbine high-temperature components (such as turbine blades, shrouds, combustor liner, exhaust nozzle, etc.), with high oxidation and creep resistance and outstanding mechanical performance at elevated temperatures but lower density than single crystals. Within the CMCs, ceramic fibers serve as the major performance support. Polymer derived ceramics (PDCs) or polymer derived ceramic route is an innovated ceramic production technique, developed over the last half-century, that begins with the synthesis or the selection of monomer molecules (therefore also known as molecular methods); fine-tunes at the precursor stage; shapes during crosslinking stage; and converts the organic components into inorganic ceramics via pyrolysis. This method enables the synthesis of uniform ceramic fibers at a much lower temperature and easier processing condition than conventional powder-based synthesis. PDC fibers (SiC, Al₂O₃, BN, etc.) have already shown great potential in high-temperature applications as reinforcement of CMCs. This thesis focus on the synthesis and characterization of ceramic fibers from silicon-based liquid-phase precursors. The fibers are drawn using two different techniques (hand spinning and electrospinning), that are able to deliver individual ceramic fibers and ceramic fiber mats. The first approach demonstrates the preparation of SiOCN fibers from a hybrid precursor of 1,3,5,7-tetramethyl-1,3,5,7-tetravinylcyclotetrasilazane (referred to as TTCSZ) and polyacrylic acid (PAA) using hand spinning. Later, SiOC fiber mats are synthesized via electrospinning from various cyclic preceramic oligomers or monomers with polyvinylpyrrolidone (PVP) as a spinning reagent. The fiber products are systematically investigated molecular structures, performances, and chemical bonding progression of the fibers at each processing stage (spinning, crosslinking, and pyrolysis). The approaches for ceramic fiber spinning and pyrolysis processes utilize cyclic siloxanes and silazanes for the first time as the ceramic precursors that are low cost and available in large quantities. The products show great potential in high-temperature applications as well as other applications such as energy storage.
Keywords: Polymer-derived ceramics; SiOC; Fibers; Electrospinning; Hand spinning; Cyclic precursors